Who governs Southern Europe? : regime change and ministerial recruitment, 1850-2000 - Almeida, Pedro Tavares de; Pinto, António Costa; Bermeo, Nancy Gina, 1951- (F. Cass, 2003)
This collection is a comprehensive, empirical account of the composition and patterns of recruitment of ministerial elites in Southern Europe throughout the last 150 years, thus encompassing different historical circumstances and political settings.
Keywords: Europe, Southern -- Politics and government.; Elite (Social sciences); Power (Social sciences); Spain -- Politics and government.; Portugal -- Politics and government.; Italy -- Politics and government.; Greece -- Politics and government.; Élite (Sciences sociales); Pouvoir (Sciences sociales); Espagne -- Politique et gouvernement.; Portugal -- Politique et gouvernement.; Italie -- Politique et gouvernement.; Grèce -- Politique et gouvernement.; HISTORY -- Historical Geography.; Politics and government; Southern Europe; Greece; Italy; Portugal; Spain